State examinations in mathematics and evaluation standards - Šinkūnas, Juozas; Urbonas, A.P. (Lietuvos matematikos rinkinys, 2005)
Results of the mathematics state examination are analyzed and compared with evaluation standards.
Keywords: examination; evaluation standards